Human Rights in the Age of Platforms - Jørgensen, Rikke Frank (Information Policy, 2019)
Scholars from across law and internet and media studies examine the human rights implications of today's platform society. Today such companies as Apple, Facebook, Google, Microsoft, and Twitter play an increasingly important role in how users form and express opinions, encounter information, debate, disagree, mobilize, and maintain their privacy. What are the human rights implications of an online domain managed by privately owned platforms? According to the Guiding Principles on Business and Human Rights, adopted by the UN Human Right Council in 2011, businesses have a responsibility to respect human rights and to carry out human rights due diligence. But this goal is dependent on the willingness of states to encode such norms into business regulations and of companies to comply. In this volume, contributors from across law and internet and media studies examine the state of human rights in today's platform society. The contributors consider the "datafication" of society, including the economic model of data extraction and the conceptualization of privacy. They examine online advertising, content moderation, corporate storytelling around human rights, and other platform practices. Finally, they discuss the relationship between human rights law and private actors, addressing such issues as private companies' human rights responsibilities and content regulation. Contributors Anja Bechmann, Fernando Bermejo, Agnès Callamard, Mikkel Flyverbom, Rikke Frank Jørgensen, Molly K. Land, Tarlach McGonagle, Jens-Erik Mai, Joris van Hoboken, Glen Whelan, Jillian C. York, Shoshana Zuboff, Ethan Zuckerman Open access edition published with generous support from Knowledge Unlatched and the Danish Council for Independent Research.